Level of fibrinogen, D-dimers and C-reactive protein, and correlations between these parameters in ischemic and haemorrhagic stroke - Jedrzej Jan Warpechowski; Joanna Jamiołkowska; Michał Ilnicki; Karolina Michalczuk; Agata Czarnowska; Joanna Kulikowska; Katarzyna Kapica-Topczewska; Jan Kochanowicz; Alina Kułakowska (Medycyna Ogólna i Nauki o Zdrowiu, 2021)
Introduction and objective Fibrinogen (FIB) and C-reactive protein (CRP) play an important role in any inflammatory response. FIB levels may be higher in stroke patients compared to non-stroke patients. CRP is used to detect inflammation due to its high sensitivity in aseptic inflammation. Blood levels of d-dimer (DD) are used to determine the amount of fibrin formed and distributed. Inflammation may play an important role in the pathogenesis of haemorrhagic stroke causing primal da-mage, and in ischemic stroke causing secondary damage due to a decrease in perfusion in the brain. The aim of the study is to prove the hypothesis that the inflammatory process is involved in the pathogenesis of ischemic and haemorrhagic stroke.